Fragility Curves for Low- and Mid-rise Buildings in Malaysia. (2015) - Saruddin, Siti Nur Aqilah; Nazri, Fadzli Mohamed
Abstract: In this paper, a study is presented on development of fragility curve for Malaysian low- and mid-rise buildings that are reinforced concrete and steel moment–resisting frames. Two prototype models, which include three- and six-story frame structures with different types of material, were designed based on Eurocodes. Incremental dynamic analysis (IDA) was conducted under seven sets of ground motion records, and scaling peak ground acceleration increased every 0.05 g until it achieved 0.6 g. The software SAP2000 was used to perform IDA. Five levels of performance based seismic designs, namely, operational phase, immediate occupancy, damage control, life safety, and collapse prevention, were considered to assess structural performance. Seismic fragility curves were developed for structural models with different types of material and height.